The sexy vegan cookbook : extraordinary food from an ordinary dude - Patton, Brian L., 1978- (New World Library, 2012)
"Ordinary dude" Brian Patton became a vegan when he discovered that he could not only survive but thrive without taking the life of another being. Here is his collection of delicious, hearty, and satisfying meals.